Improved Functionality of Poly(3,4-Ethylenedioxythiophene):Poly(Styrenesulfonate)/HeptaCoordinated Organotin Complex Films via Graphene Applied to Organic Solar Cell Fabrications - Sánchez Vergara, María Elena; Zubillaga Serrano, Rafael Imanol; Hamui, Leon; Galván Hidalgo, José Miguel; Cosme, Ismael; Gómez, Elizabeth (Frontiers in Materials, 2022)
Enhanced transparency, conductivity, and stability are some of the most important factors to consider in order to prepare transparent electrodes (TEs) and hole transport layer (HTL) for organic solar cells. In this study, the transparency, optical, and electrical behavior of hybrid films formed by poly(3,4-ethylenedioxythiophene):poly (styrenesulfonate) (PEDOT:PSS) and heptacoordinated organotin (IV) complexes was improved by introducing graphene. The films were deposited by spin-coating and subsequently characterized by infrared and Raman spectroscopy, and by scanning electron microscopy (SEM) and atomic force microscopy (AFM). All the hybrid films transmitted more than 70% of light in the 600–1,000 nm wavelength region, and the optical band gap obtained is in the range of 2.64 and 3.09 eV. In addition, bathophenanthroline (BPhen) was introduced as an electron transport layer (ETL) in order to study the solar cell with complete architecture, conformed by glass/ITO/PEDOT:PSS-graphene-complex/BPhen/Ag. By incorporating the BPhen, the J–V curve current density values were increased, showing a conductivity change of as much as 2.1 × 10−4 S/cm, and under illuminated conditions a more pronounced J–V curve variation (as much as 2.5 × 101 A/cm2) was observed. In closing, the devices were subjected to accelerated lighting conditions to determine the stability and operating capacity of the solar cells. The electrical behavior of the devices changed. Within the first 2 h, the electrical behavior improved, where the organotin complex without a substituent (complex-a) device presents higher stability than the complex with the chloride substituent (complex-b) device due to the chloride radical interacting with the BPhen. However, the electrical behavior degraded after 4 h almost eight orders of magnitude in current density due to device films and interface degradation.